Developing a Virtual Reality- and Lean-based Training Platform for Productivity Improvement of Scaffolding Installation in Liquefied Natural Gas Industry - Wang, Peng (Curtin University, 2020)
This thesis aims to integrate lean and work postures to simultaneously improve productivity and health and safety and develop a lean- and virtual reality-based platform for effective education and training in scaffolding installation in turnaround maintenance projects. It represents an effort to help on-site workers in the Liquefied Natural Gas industry identify waste activities and achieve a balanced improvement in both productivity and health and safety through improved training in a virtual platform.